A Pragmatic Stylistic Analysis of the poem‘O Captain! My Captain!’ by Walt Whitman - Murtias, Latifa Nanda; Silpandi, Neviya; Batubara, Vinjellina; Ahmad, Sophie Meilatifah; Rangkuti, Rahmadsyah (Journal of English Language and Education, 2025)
This study analyzes the poem O Captain! My Captain! by Walt Whitman using pragmatic stylistic analysis based on speech acts, deixis, and implicature. It adopts a qualitative descriptive analytic model and seeks to answer the question of how Whitman’s linguistic choices affect the emotional and communicative dimensions of the poem. It’s found that expressive, directive, and commission speech acts create feelings of grief, admiration, and a promise of remembrance. Personal, temporal, and spatial deixes emphasize the relationship between the speaker, the deceased leader, and the historical context. The message of the poem, the irony of victory hidden in deep loss, is revealed through implicature. This study shows that Whitman’s choice of language in the elegy touches the hearts of the nation. The study reveals the importance of carrying out a pragmatic stylistic analysis of poetry to discover more meanings behind the text.